The vampire in Europe - Summers, Montague, 1880-1948 (Gramercy Books, 1996)
Renowned occultist and clergyman Montague Summers explores the realm of Dracula and comes up with some shocking possibilities as well as "true tales" of terror from places including England, Ireland, Hungary, Bulgaria, Romania, and Greece.--From publisher description.